A contemporary look at business ethics - Sims, Ronald R. (Contemporary human resource management., 2017)
A Contemporary Look at Business Ethics provides a 'present day' look at business ethics to include the challenges, opportunities and increased need for ethical leadership in today's and tomorrow's organizations. The book discusses current and future business ethics challenges, issues and opportunities which provides the context leaders and their organizations must navigate.The book includes an in-depth look at lessons learned about the causes of unethical behavior by examining a number of real-world examples of ethical scandals from around the world that have taken place over the past few decades. The analysis of the various ethical scandals focuses on concepts like ethical versus unethical leadership, received wisdom, the bottom-line mentality, groupthink and moral muteness, all of which contribute to the kind of organizational culture and ethical behavior one finds in an organization. The book discusses ethical decision making in general and the increased role of religion and spirituality, in confronting unethical behavior in contemporary organizations.The book also takes an in-depth look at the impact ethical scandals have on employees and more specifically the psychological contract and person-organization ethical fit with the goal of identifying, along with other things, what leaders can do to restore relationships with employees and rebuild the organization's reputation in the eyes of various stakeholders.